Incidence of the shading, bioregulators and biostimulant on the growth and yield of Mombaza grass (Panicum maximum Jacq.) - Jácome-Gómez, Leonardo R.; Ramírez-Villalobos, Maribel del C. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Shading (S), bioregulators (BR) and biostimulants (BS) techniques are alternatives that promote sprouting and production of grass. The objective was to evaluate the effect of S, BR and BSt on the growth and yield of Mombaza grass in Ecuador. A complete randomized block design, with split plot arrangement and three replications, was used, the main plot represented by condition S (S1: full solar exposure, S2: shade of trees) and secondary one by BR and BS application (A0: control; A1: minimum doses of BR, 250 mL.ha-1 Cytokin + 10 g.ha-1 New Gibb 10 %; A2: maximum doses of BR, 500 mL.ha-1 Cytokin + 20 g.ha-1 New Gibb 10 %;  A3: commercial dose of BS Algamar, seaweed, 750 g.ha-1). Three cuts of grass were made, 35 days after staring experiment; in each one, tiller height (TH), number of tillers×m-2 (NTM) and stems×tiller-1 (NST), and dry matter yield (DMY) were evaluated. It is found effects (P<0.05) of S on the four variables in each cut; and application of BR and BS on TH in cuts 1, period of least precipitation. It is concluded that the grass cultivated in S1 increased the growth and DMY in cuts 1, 2 and 3 (0.180, 0.300 y 0.398 kg.m-2). NTM was stimulated with S2 and TH with the minimum dose of BR.